MENGINTEGRASIKAN KECERDASAN BUATAN DALAM PENDIDIKAN BAHASA INGGRIS ISLAM - Afri Yulianti; Kartika Meilisa; Nur Afriliana Putri; Rabiah Al Adawiyah; Seila Egia Andini (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly influenced English language teaching in Islamic educational institutions. AI-powered tools such as ChatGPT, Grammarly, and QuillBot have enhanced learning by making it more flexible, interactive, and efficient. However, their widespread adoption also raises ethical concerns, particularly regarding academic integrity and the core values of Islamic education. This study aims to examine the opportunities, challenges, and ethical perspectives surrounding the integration of AI into Islamic English Education. Employing a qualitative descriptive approach through library research, the study analyzes relevant books, scholarly articles, and previous research. The findings indicate that AI enhances personalized learning, digital literacy, and the effectiveness of English language instruction. Nevertheless, it also poses risks, including plagiarism, technological dependency, diminished critical thinking skills, and the dissemination of inaccurate information. From an Islamic ethical perspective, AI implementation should be guided by the principles of sidq (honesty), amanah (responsibility), and adab (proper conduct). Therefore, AI should function as a complementary pedagogical tool rather than a substitute for intellectual engagement and character development. Balancing technological innovation with Islamic moral values is essential to fostering effective, ethical, and meaningful English language learning.